Salivary proteins associated with periodontitis in patients with type 2 diabetes mellitus. - Chan, H.H.; Rahim, Z.H.; Jessie, K.; Hashim, Onn Haji; Taiyeb-Ali, Tara Bai (2012)
A series of binary tellurite based glasses (Bi(2)O(3))(x) (TeO(2))(100-) (x) was prepared by melt quenching method. The density, molar volume and refractive index increase when bismuth ions Bi(3+) increase, this is due to the increased polarization of the ions Bi(3+) and the enhanced formation of non-bridging oxygen (NBO). The Fourier transform infrared spectroscopy (FTIR) results show the bonding of the glass sample and the optical band gap, E(opt) decreases while the refractive index increases when the ion Bi(3+) content increases.